De-routinization of jobs and polarization of earnings: Evidence from 35 countries - Maximilian Longmuir; Carsten Schröder; Matteo Targa (Luxembourg Income Study (LIS), 2020)
The job polarization hypothesis suggests a U-shaped pattern of employment growth along the earnings/skill distribution, which is driven by simultaneous growth in the employment of high-skill/high-earnings and low-skill/low-earnings occupations due to Routine-Biased Technological Change (RBTC) [Acemoglu and Autor, 2011]. An aspect of both high social and political relevance is the implications of job polarization and technological change for earnings distributions. In this paper, we put the RBTC trend into perspective by decomposing earnings growth into parts attributable to job polarization and other components. Using a novel harmonized dataset provided by the Luxembourg Income Study and the Economic Research Forum, we find evidence for employment polarization in 30 out of the 35 countries under analysis, in both developed and developing economies. However, the effects of this displacement in the workforce have no polarizing effect on the earnings distribution in 33 countries, once we account for between and within variation in occupational classes returns.
Keywords: D3; J3; J8; 330; job polarization; technological change; earnings and wage distribution; Luxembourg Income Study database; Economic Research Forum database